Counseling model for recovery of former members of abusive religious groups in the Philippines - Valenzuela, Marita C.; Ho, Leticia P.; Soria, Robinson C.; De Guzman, Ligaya S. (2007)
The research revealed that the combination of the individual's vulnerabilities at the time of conversion plus the power of the persuader account for the person succumbing to cults as well as staying in it. Such vulnerabilities include age, a need to belong, dysfunctions in the primary social support system as well as cultural predisposition, e.g. an unassertive nature, traditional religiosity, unquestioning respect for authority and group thinking. Results of the personality inventory showed that although there is no clear personality type that joins cults, it is nonetheless important to be cognizant of the particular personality traits of affiliation, nurturance and succorance, which if pronounced would make people naturally prone to being attracted to cults' offerings.
"March 2007."
Thesis (M.A. Education : Guidance)--University of the Philippines Diliman.
Keywords: Ritual abuse victims -- Counseling of -- Philippines; Ritual abuse -- Philippines; Faith-based human services -- Philippines